Method for determining the fractal properties of textual information for the presence of informational impact - Barannik, Vlad.; Belikova, T. (видавництво "МАДРИД", 2019)
Analysis of modern interstate conflicts, trends in the development of forms of warfare. It is shown that the op-position is characterized by various forms, is hidden in nature and is carried out mainly in the political, economic, informational and other spheres. It is proved that a significant part of the hybrid wars are informational and informational and psychological operations used for the purpose of a destructive impact on society using information and communication space and technology. The article expresses the need to use the method of the fractal properties of the text to counter the hidden informational and informational and psychological effects, as an integral part of the national security of the state.
Keywords: automation; psychological operations; information security; manipulation